to solve for the x you can first simplify ∛27 to 3 so the equation is now: x³+1=3(3)
then simplify more so x³=91 which is then x³=8 and when you simplify that x=2
to solve for the y now you can plug in 8 for x³ so now the equation is 8+y³=5√49
simplify √49 to 7 which now makes the equation 8+y³=5(7)
simplify even more making the equation now y³=358 which is then y³=27 and simplify that and y=3
then simplify more so x³=91 which is then x³=8 and when you simplify that x=2
to solve for the y now you can plug in 8 for x³ so now the equation is 8+y³=5√49
simplify √49 to 7 which now makes the equation 8+y³=5(7)
simplify even more making the equation now y³=358 which is then y³=27 and simplify that and y=3

x=2 and y=3 :)
Report Abuse

∛27 = 3 and √49 = 7, so:
x³+1=9 and x³+y³=35
Solve for x³ in the first equation to get x³=8. Therefore, x = 2. Now plug this into the second equation:
8 + y³ = 35, now solve for y:
y³=27
y = 3.
So your solutions are y = 3 and x = 2.
x³+1=9 and x³+y³=35
Solve for x³ in the first equation to get x³=8. Therefore, x = 2. Now plug this into the second equation:
8 + y³ = 35, now solve for y:
y³=27
y = 3.
So your solutions are y = 3 and x = 2.

square root = power of 1/2
third root = 1/3
so 27^(1/3) = 3
3*3 = 9
so the first one becomes
x^3 = 8
x = 2
plug it in the second equation to get y. sqrt of 49 = 7
2^3 + y^3 = 5*7
y^3 = 35  8 = 27
y = 3
third root = 1/3
so 27^(1/3) = 3
3*3 = 9
so the first one becomes
x^3 = 8
x = 2
plug it in the second equation to get y. sqrt of 49 = 7
2^3 + y^3 = 5*7
y^3 = 35  8 = 27
y = 3